2021
DOI: 10.1029/2021gl094541
|View full text |Cite
|
Sign up to set email alerts
|

Winter Snow Depth on Arctic Sea Ice From Satellite Radiometer Measurements (2003–2020): Regional Patterns and Trends

Abstract: While an unambiguous climate change signature has been observed in Arctic sea ice coverage (Andersen et al., 2020;Stroeve et al., 2007), it has been difficult to quantify the changes in snow depth over the sea ice region (Webster et al., 2018). This holds in spite of snow accumulation being one of the most important geophysical parameters to understand Arctic climate, being related to albedo feedback, ice cover insulation, and associated heat transfer effects (Curry et al., 1995;Ledley, 1991;Webster et al., 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Recently, in addition to the FYI area, the snow depth during the freezing period on multiyear sea ice (MYI) has also reduced significantly compared to the W99 snow depth [23]- [26]. This implies that the mW99 also causes an overestimation of the snow depth over the MYI area.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, in addition to the FYI area, the snow depth during the freezing period on multiyear sea ice (MYI) has also reduced significantly compared to the W99 snow depth [23]- [26]. This implies that the mW99 also causes an overestimation of the snow depth over the MYI area.…”
Section: Introductionmentioning
confidence: 99%
“…In mW99, this snow depth variability exists only in regions where the sea ice type changes. Additionally, recent modeling and satellite observational studies have shown that snow depth trends differ according to region, with an increase and decrease over the western and eastern Arctic Ocean, respectively [26], [27]. Therefore, snow depth that varies spatiotemporally (also referred to as "dynamic snow depth") is preferable for the estimation of sea ice thickness [28], [29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several ways to measure the aerosol composition, such as remote sensing from satellite or ground-based instruments, in-situ measurement on the surface or from aircraft. Satellite instruments can provide measurements of large areas but are not very suitable in the Arctic due to the frequent existence of clouds and snow/ice on the surface, which make the measurements challenging (Lee et al, 2021). The in-situ measurements provide much more accurate measurements, but are often limited to the planetary boundary layer and a distinct position.…”
Section: Introductionmentioning
confidence: 99%